2020
DOI: 10.1016/j.jand.2020.06.021
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Replacing Refined Grains with Whole Grains on Cardiovascular Risk Factors: A Systematic Review and Meta-Analysis of Randomized Controlled Trials with GRADE Clinical Recommendation

Abstract: Grains & Legumes Nutrition Council of Australia provided critical revision and feedback on the proposed review methodology; but had no contribution to the analysis or interpretation of results. All authors declare no existing or potential conflicts of interest.Funding statement: This study received funding from Grains & Legumes Nutrition Council of Australia. Research Snapshot:Research question: In adults with or without chronic disease and/or associated risk factors, do interventions providing whole grain or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 51 publications
3
39
0
1
Order By: Relevance
“…The greater use may also relate to perceptions regarding consumer understanding or may simply be aligned with research outcomes for whole grains and CVD. The benefits of regular consumption of whole grain foods are well documented [ 4 , 36 , 37 , 38 , 39 ], with every 16 g increase (one serving) associated with a 9% reduction in cardiovascular disease risk [ 40 , 41 ]. In addition to exploring the Australian consumer understanding of beta glucan claims, a comparison to more general whole grain claims would also be of value especially as whole grain claims are growing rapidly, with a 39% increase in the number of products making whole grain claims in Australia in the past 5 years [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The greater use may also relate to perceptions regarding consumer understanding or may simply be aligned with research outcomes for whole grains and CVD. The benefits of regular consumption of whole grain foods are well documented [ 4 , 36 , 37 , 38 , 39 ], with every 16 g increase (one serving) associated with a 9% reduction in cardiovascular disease risk [ 40 , 41 ]. In addition to exploring the Australian consumer understanding of beta glucan claims, a comparison to more general whole grain claims would also be of value especially as whole grain claims are growing rapidly, with a 39% increase in the number of products making whole grain claims in Australia in the past 5 years [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antidiabetic properties, decreased inflammation, and the modulation of lipid metabolism and oxidative stress have been documented in in vitro studies and clinical trials investigating health benefits of consuming brown rice (38) . A recent systematic review and meta-analysis of randomized controlled trials found that, compared with white rice, brown rice led to an improvement in triacylglycerol levels (-1.6 mg/dL) in interventions ranging Accepted manuscript from 150 to 400g of cooked rice (39) . One serving of brown rice per day was also associated with reductions in type 2 diabetes risk (Hazard ratio [HR] 0.72) in three large prospective studies from the United States of America (USA); however the association was no longer significant after adjusting for BMI (40) .…”
Section: Discussionmentioning
confidence: 99%
“…Higher nutrient density of whole grains may help explain some of the observed health benefits. Meta-analysis of up to 22 randomized clinical trials ( 49 ) showed that replacing refined grain or placebo with whole grain led to improvements in plasma lipid profiles that were attributed to whole-grain oats. Replacing refined grains with whole grains also improved glycated hemoglobin (a marker of diabetes risk) and C-reactive protein (a marker of inflammation).…”
Section: Current Status Of Knowledgementioning
confidence: 99%